Students' Math Literacy in Solving PISA-Like Problems in Papuan Local Context - Muhammad Noor Kholid; Mardiana Nissa (STAI Hubbulwathan Duri, 2022)
Mathematical literacy in Indonesia is still relatively low. Student achievement in PISA questions is also still not adequate. Mathematical literacy is not limited to the ability to apply quantitative aspects of mathematics, it employs knowledge of mathematics in a broad sense. Mathematical literacy skills are closely related to interpreting problems related to local contexts into mathematical problems. This study aims to describe students' mathematical literacy activities in solving problems similar to PISA in the regional context; the context in which this research is desired is the local Papuan context. The research method employed is the descriptive qualitative method. The samples were 8th graders of SMP Batik Program Khusus Kartasura, totaling six students. Data was collected using a written test consisting of two items of PISA-like problems, observations, and interviews. This research produces problems similar to PISA within the local context of Papua. PISA-like questions are declared to be valid, simple, and have the potential to determine students' mathematical literacy abilities. The PISA-like problems are valid based on the review by experts in the appropriate field in terms of aspects, content, structure, and language. This PISA-like problem was also developed based on seven basic mathematical abilities that employ mathematical literacy. We successfully concluded that the dominant aspects for students are making assumptions and conceptualizing. While the parts of structuring and formulating a model are not dominant. In addition, PISA-like problems have more potential effect on determining students' mathematical literacy.